Active adsorption performance of planetary ball milled Saudi Arabian bentonite clay for the removal of copper ions from aqueous solution. (18th October 2021) - Abutaleb, Ahmed; Eldoma, Mubarak A.; Imran, Mohd; Taha, Kamal K.; Bakather, Omer Y.; Zouli, Nasser; Hegazi, Salah Eldeen F.; Hassan, Mohamed
Abstract: We report the role of local bentonite clay in the removal of Cu 2+ ions from aqueous solution. The fine bentonite clay powder was analysed by XRD, FTIR, SEM and DLS analysis techniques. Further, the adsorption experiments were carried out by varying many factors such as weight and size of bentonite clay, residence time, p H of the solution, stirring rate, temperature, and flow rate. The optimum conditions for effective removal of Cu 2+ ions was 1 g dose of bentonite and 63 μm size of bentonite, 50 minutes of residence time and 50 °C temperature at p H 3 with a flow rate of 1 L/min. The data fitted well the Freundlich model and a maximum adsorption capacity of 61.72 mg/g has been obtained. The value of Gibbs free energy changes ( ), enthalpy changes ( ) and entropy changes ( S°) were found to be, and, respectively.